A novel approach for domino effects modeling and risk analysis based on synergistic effect and accident evidence. (November 2020) - Ding, Long; Khan, Faisal; Ji, Jie
Highlights: A novel approach for domino effects modeling and risk analysis. Fire accident evidence and synergistic effects are considered. Energy accumulation effect is used to assess the domino effect risk. A visible image of domino evolution and associated risk are presented. Abstract: Modeling the spatial-temporal evolution of domino effects and analyzing its risk could guide risk prevention and control. In the present work, a novel approach is proposed to model the spatial-temporal evolution and perform a risk analysis of fire-induced domino effects based on synergistic effect and accident evidence. The approach takes fire accident evidence into account to model the synergistic effect of burning units. The receivable thermal dose is adopted as the failure criterion of endangered units to consider heat energy accumulation. The time to failure and escalation probability are used to assess domino effect risk. The proposed approach is effective to model the dynamic evolution of accident propagation, and the results provide a visible image of domino effect evolution and associated risk, and also the results are helpful to identify the most vulnerable unit and the most dangerous units. A case study is illustrated to demonstrate the credibility and applicability of the proposed approach.